2022
DOI: 10.3390/nu14235186
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Vitamin D with Peptide Hormones with Emphasis on Parathyroid Hormone, FGF23, and the Renin-Angiotensin-Aldosterone System

Abstract: The seminal discoveries that parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) are major endocrine regulators of vitamin D metabolism led to a significant improvement in our understanding of the pivotal roles of peptide hormones and small proteohormones in the crosstalk between different organs, regulating vitamin D metabolism. The interaction of vitamin D, FGF23 and PTH in the kidney is essential for maintaining mineral homeostasis. The proteohormone FGF23 is mainly secreted from osteoblasts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…1,25(OH)2D3 production in the kidney is stimulated by 1α-hydroxylase, which is regulated by parathormone (PTH) as a part of feedback loop between kidney and parathyroid gland. Moreover 1,25(OH)2D3 and phosphate stimulate fibroblast growth factor 23 (FGF23) secretion from bone which in turn inhibits transcription of 1α-hydroxylase and promotes transcription of 24-hydroxylase (an enzyme responsible for VD catabolism) [32,33]. The metabolism of 25(OH)D3 in kidney is still not yet fully elucidated and there are gaps in our knowledge to be fulfilled and presented lack of association between VD concentration and CVD may be caused by the abovementioned hormonal interplay having an impact on production of active form of VD and further clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH)2D3 production in the kidney is stimulated by 1α-hydroxylase, which is regulated by parathormone (PTH) as a part of feedback loop between kidney and parathyroid gland. Moreover 1,25(OH)2D3 and phosphate stimulate fibroblast growth factor 23 (FGF23) secretion from bone which in turn inhibits transcription of 1α-hydroxylase and promotes transcription of 24-hydroxylase (an enzyme responsible for VD catabolism) [32,33]. The metabolism of 25(OH)D3 in kidney is still not yet fully elucidated and there are gaps in our knowledge to be fulfilled and presented lack of association between VD concentration and CVD may be caused by the abovementioned hormonal interplay having an impact on production of active form of VD and further clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of Ca and Pi in serum were determined to evaluate mineral and bone metabolism. FGF23, which is secreted primarily by osteoblasts and osteocytes, is a physiological regulator of circulating phosphate and vitamin D levels, and it has been reported that the serum level of FGF23 is increased with an increased dietary phosphate load (Vogt et al, 2019;Latic and Erben, 2022). It is also commonly believed that CKD-MBD is associated with the elevation of serum i-PTH and FGF23 levels (Cannata-Andía et al, 2021).…”
Section: Ca and Pi Levels In Serum Were Altered In The Three Ckd-mbd ...mentioning
confidence: 99%
“…Particularly essential is an endocrine loop where FGF23, parathyroid hormone (PTH), 13,14 and 1,25(OH) 2 D 3 15,16 influence each other. 17 FGFR1 signaling 18 and local factors including sclerostin 19 are further important regulators of FGF23 production in bone. Post-translational regulation of FGF23 depends on the balance of glycosylation and phosphorylation through GALNT3 and FAM20C, respectively.…”
Section: Introductionmentioning
confidence: 99%